FBM Round Table Dialogue for postgraduate research program - UiTM, Faculty of Business and Management (UiTM, 2023)
On September 11, 2023, the Faculty of Business and Management held a Round Table Dialogue for its three postgraduate research programs: Doctor of Philosophy (Business Management), Doctor of Philosophy (Office Systems Management), and Master of Science (Business Management). The event took place at Hotel UiTM Shah Alam, running from 9.00 a.m. to 2.30 p.m.